Multi-Agent-Based Simulation XV International Workshop, MABS 2014, Paris, France, May 5-6, 2014, Revised Selected Papers - Grimaldo, Francisco; Norling, Emma.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 15th International Workshop on Multi-Agent-Based Simulation, MABS 2014, held in Paris, France, in May 2014. The workshop was held in conjunction with the 13th International Conference on Autonomous Agents and Multiagent Systems, AAMAS 2014. The 17 revised full papers included in this volume were carefully selected from numerous submissions. The papers are organized in topical sections on simulation methodologies, simulation of social behaviour, data and multi-agent-based simulation and applications.
Simulation Methodologies -- Simulation of Social Behaviour -- Data and Multi-agent-Based Simulation -- Applications.
Keywords: Artificial intelligence; Computer simulation; Computers; Artificial Intelligence; Simulation and Modeling; Computation by Abstract Devices